2017
DOI: 10.1002/chem.201700437
|View full text |Cite
|
Sign up to set email alerts
|

Carbonyl Activation by Borane Lewis Acid Complexation: Transition States of H2 Splitting at the Activated Carbonyl Carbon Atom in a Lewis Basic Solvent and the Proton‐Transfer Dynamics of the Boroalkoxide Intermediate

Abstract: By using transition-state (TS) calculations, we examined how Lewis acid (LA) complexation activates carbonyl compounds in the context of hydrogenation of carbonyl compounds by H in Lewis basic (ethereal) solvents containing borane LAs of the type (C F ) B. According to our calculations, LA complexation does not activate a ketone sufficiently enough for the direct addition of H to the O=C unsaturated bond; but, calculations indicate a possibly facile heterolytic cleavage of H at the activated and thus sufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Overall, Δ E H and Δ G H consistently indicate the plausibility of the hydrogen‐bonded couples considered herein, and this is in agreement with the aforementioned literature (see Introduction) describing participation of OH⋅⋅⋅O=C bonding motifs in reaction mechanisms. Since association in solvent is quite a complex process, taking the fully separated counterparts as the reference point is a commonly used approach, but it is inherently crude and it can produce an overestimation of the entropy change, Δ S , contributing to the calculated Δ G H ; thus, the magnitude of Δ G H can be substantially underestimated …”
Section: Resultsmentioning
confidence: 99%
“…Overall, Δ E H and Δ G H consistently indicate the plausibility of the hydrogen‐bonded couples considered herein, and this is in agreement with the aforementioned literature (see Introduction) describing participation of OH⋅⋅⋅O=C bonding motifs in reaction mechanisms. Since association in solvent is quite a complex process, taking the fully separated counterparts as the reference point is a commonly used approach, but it is inherently crude and it can produce an overestimation of the entropy change, Δ S , contributing to the calculated Δ G H ; thus, the magnitude of Δ G H can be substantially underestimated …”
Section: Resultsmentioning
confidence: 99%
“…An alternative mechanism for splitting of the H 2 molecule and subsequent facile hydrogenation of carbonyl compounds has been proposed recently. [24][25][26] The mechanism starts with the activation of the C=O group by complexation of a Lewis acid (B(C 6 F 5 ) 3 ) or throughout protonation of the oxygen of the C=O. A ketone sharing a proton with a solvent molecule (solvatedproton) is a common feature of mechanistic consideration in FLP-hydrogenation of carbonyl compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Quantum chemical calculations showed that upon external activation of the carbonyl group, its Lewis acidity enhances and the carbon atom can behave like a Lewis acidic center to further activate the H 2 molecule in cooperation with solvent as the Lewis base. An alternative mechanism for splitting of the H 2 molecule and subsequent facile hydrogenation of carbonyl compounds has been proposed recently [24‐26] . The mechanism starts with the activation of the C=O group by complexation of a Lewis acid (B(C 6 F 5 ) 3 ) or throughout protonation of the oxygen of the C=O.…”
Section: Introductionmentioning
confidence: 99%
“…[3] A recent computational study reported by Heshmat et al suggests, based on GGA DFT computations, a mechanism for the H 2 splitting in which the carbonyl carbon atom of a ketone coordinated to B(C 6 F 5 ) 3 acts as a Lewis acid in conjunction with an ether molecule of the solvent as a Lewis base. [4] Concerted hydrogenations via a pericyclic six-membered transition state were the generally accepted mechanistic picture for ketone reductions catalyzed by Noyori-type bisphosphinebisamino-ruthenium complexes (Scheme 2). [5] Inspired by these systems, Li et al computationally designed a bifunctional metal-free system, that should, according to the computations, allow concerted hydrogen transfers to carbonyl compounds (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…Based on DFT computations, Das et al proposed a stepwise mechanism in which the protonation of the ketone by the protonated ether precedes hydride transfer, which is, however, somewhat conflicting with the experimentally determined p K A values of a protonated ether and a protonated ketone . A recent computational study reported by Heshmat et al suggests, based on GGA DFT computations, a mechanism for the H 2 splitting in which the carbonyl carbon atom of a ketone coordinated to B(C 6 F 5 ) 3 acts as a Lewis acid in conjunction with an ether molecule of the solvent as a Lewis base …”
Section: Introductionmentioning
confidence: 99%